The Effect of Inclines on Joint Angles in Stroke Survivors During Treadmill Walking - Zhang, Xin; Lu, Yanting; Chien, Jung Hung; Fu, Chenlei; Zhou, Zhe; Li, Hua; Hu, Gongwei; Sun, Tianbao (Frontiers in Neurology, 2022)
Stroke severely affects the quality of life, specifically in walking independently. Thus, it is crucial to understand the impaired gait pattern. This gait pattern has been widely investigated when walking on a level treadmill. However, knowledge about the gait pattern when walking on inclines is scarce. Therefore, this study attempted to fulfill this knowledge gap. In this study, 15 stroke survivors and 15 age/height/weight healthy controls were recruited. The participants were instructed to walk on three different inclines: 0°, 3°, and 6°. The participants were required to walk on each incline for 2 min and needed to complete each incline two times. The dependent variables were the peak values for ankle/knee/hip joint angles and the respective variability of these peak values. The results showed that an increment of the incline significantly increased the peak of the hip flexion and the peak of the knee flexion but did not affect the peak values of the ankle joints in the paretic leg in these stroke survivors. In comparison with the healthy controls, lower hip extension, lower hip flexion, lower knee flexion, and lower ankle plantar flexion were observed in stroke survivors. A clinical application of this work might assist the physical therapists in building an effective treadmill training protocol.